Application of Refractive Index Mixing Rules in Binary Liquid Mixture - Saxena, M.C. (Asian Journal of Chemistry, 2010)
A comparative study of five mixing rules of refractive index hasbeen carried out to test their validity for four binary liquid mixturesat wide range of composition and temperature. Comparison of variousrules has been expressed in terms of average percentage deviation.All mixing rules perform well within the limit of experimentalerror but the performance of Heller's relation (H) and Wiener'srelation (W) are comparatively better than those of others.